The Field of Investment Advice: The Social Forces That Govern Equity Analysts - Millo, Yuval; Spence, Crawford; Valentine, James (The Accounting Review, 2023)
ABSTRACT Literature on equity analysts presents a conundrum: analysts are seen as influential market participants, yet researchers widely criticize them for their bias and inaccuracy. Studies drawing from economic frames struggle to explain this. Therefore, we develop a new conceptualization that positions analysts as actors operating in a social field. Drawing on a qualitative study involving 70 interviews with analysts and portfolio managers, we offer two broad insights. First, we identify long-term interpersonal and interinstitutional ties between buy-side and sell-side actors which contribute to social inertia in the field. Second, we illustrate how sell-side analysts’ social environment is dichotomous, pushing some to converge with consensus estimates, while encouraging others to diverge. Taken as a whole, our findings contribute to the accounting literature by enriching our understanding of the social and institutional forces that govern analyst behavior.